(untitled) (International Conference on Modern Science and Scientific Studies, 2025)
Sign interpreting serves as an essential bridge between deaf and hearing communities, ensuring access to communication, education, healthcare, and participation in all aspects of society. The profession of sign language interpreting has evolved from informal community practices to a recognized field of linguistic and cultural mediation. This thesis explores the historical development, linguistic foundations, cognitive processes, ethical dimensions, and technological advancements in sign interpreting. It also analyzes the professional standards, challenges, and societal perceptions of interpreters. Through a multidisciplinary lens that combines linguistics, sociology, psychology, and communication studies, this paper highlights the importance of qualified sign interpreters in promoting inclusivity and equality. The discussion emphasizes that sign interpreting is not merely a translation of words into gestures but an act of intercultural communication that demands sensitivity to linguistic nuances, cultural contexts, and ethical boundaries. The thesis concludes by suggesting strategies for improving interpreter training, public awareness, and accessibility policies.